Determining Accuracy of IN05 Index and Its Improvement - Kuběnka, Michal (My University, 2016)
The IN05 index is probably the only one model in the world that predicts economic value added (EVA). Determining a positive or negative EVA is conducted based the level of return on equity (ROE). The threshold of the level depends on the changing value of implicit cost of equity (re). The Czech economy has undergone many changes including the economic crisis during the ten years following the creation of the IN05 index. This research uses financial data of 1,224 companies in the manufacturing sector. A very low current prediction power of IN05 was detected in prediction of prosperity. The main benefit of the research is finding a way to increase accuracy of economic value added prediction.
Stanovení přesnosti indexu IN05 a její zlepšení
Keywords: IN05 index; prosperity; economic value added; ROE; IN05 index; prosperita; ekonomická přidaná hodnota; ROE